Preparation method of multi-metal doped metal oxide / MXene composite material gas sensitive element
The gas-sensitive components of polymetal doped metal oxide and MXene composite materials were prepared by electrostatic self-assembly method, which solved the problem of high temperature and poor effect of triethylamine detection in the prior art, and achieved high sensitivity detection of triethylamine gas at low temperatures.
Patent Information
- Application Number
- CN202510122998.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, the gas-sensitive element used for triethylamine detection has a high detection temperature, resulting in poor detection effect and it is difficult to effectively detect triethylamine gas at low temperatures.
Through electrostatic self-assembly, divalent metal ions, trivalent metal ions and tetravalent metal ions are mixed in a specific proportion, and alkali liquid is added, hydrothermal reaction and calcination are carried out to obtain a polymetal doped metal oxide, which is then compounded with MXene to prepare as a gas-sensitive element. This gas-sensitive element has excellent detection effect on triethylamine at lower operating temperatures.
It realizes the detection effect of high sensitivity and fast response/recovery time for triethylamine gas at lower operating temperatures, and is suitable for real-time detection in the field of food safety.
Smart Images

Figure CN119827588A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of gas sensing, and in particular relates to a method for preparing a multi-metal doped metal oxide / MXene composite material gas sensing element. Background Art
[0002] Metal oxide semiconductors (MOS) have been widely used in the field of gas sensing due to their unique electrical properties, such as toxic and explosive gas alarms, air quality monitoring, indoor chemical pollutant monitoring, medical diagnosis through breath analysis and many other fields. These sensors have a wide range of applications due to their high sensitivity, low cost, simplicity, production flexibility and compatibility with modern electronic devices. Metal oxide semiconductors are highly sensitive to a variety of gases, can quickly detect low-concentration target gases, and have the advantages of fast response speed, rapid changes in electrical properties, and timely feedback of gas concentration changes. However, the surface gas-sensitive reaction of metal oxide semiconductors (MOS) requires thermal activation of chemically adsorbed surface oxygen, so it usually needs to work at a higher temperature, generally between 300-500°C, which not only increases energy consumption, but also limits its application in some special environments such as temperature-sensitive or explosive environments. In addition, high temperature will shorten the life of the sensor and make its performance unstable. In order to improve its gas-sensing performance, researchers have adopted the method of constructing multi-component oxides to improve its gas-sensing performance. For example, SnO 2 / NiO has high sensitivity and selectivity to triethylamine at 75℃ under ultraviolet light. 2 / CeO 2 To triethylamine than pure SnO 2 The response value is as high as 12 times, with obvious triethylamine selectivity and low detection line. It can be seen that constructing multi-component oxides can obtain gas-sensitive materials with high sensitivity, strong selectivity, low working temperature and good stability.
[0003] As a two-dimensional material, MXene is favored in electrode materials, electromagnetic shielding materials, supercapacitors, energy storage, etc. due to its rich surface functional groups, special two-dimensional layered structure, large specific surface area, high conductivity and other advantages. n+ 1X n T x (n=1-4), where M represents an early transition metal, X represents carbon or nitrogen, T x They are obtained by removing the parent three-dimensional (3D) MAX phase (M n+1 AX n ) is produced by selectively etching the A intermediate layer, such as Ti 3 AlC 2 This phase is etched by HF or HCl to obtain Ti 3 C 2T x MXene gas-sensitive materials alone are often not sensitive enough to accurately detect extremely low concentrations of target gases. They need to be compounded with other materials, modified on the surface, and other methods to improve their sensitivity. MXene nanosheets are prone to accumulation in solutions or during the preparation process, resulting in a reduction in specific surface area and fewer active sites available for gas adsorption and reaction, which in turn affects gas-sensing performance.
[0004] The preparation of MXene / MOS semiconductor composites by combining multi-component metal oxides with two-dimensional layered MXene can not only solve the MXene stacking problem, but more importantly, it can achieve the surface characteristics and functional design of the composite material by combining such multi-component metal oxides with two-dimensional layered MXene materials in the nanometer to micrometer range. The composite material combines the excellent properties of different components into one, and shows new properties that the parent material does not have.
[0005] CN118090831A discloses a gas sensor comprising an Au interdigital electrode and a Ti electrode spin-coated on the Au interdigital electrode. 3 C 2 T x -MXene@ZnO gas-sensitive composite material; CN118937421A discloses a flexible gas-sensitive sensor, comprising a flexible substrate, a first electrode layer, a composite metal semiconductor sensitive layer and a second electrode layer stacked in sequence from bottom to top, wherein the composite metal semiconductor sensitive layer comprises Ti 3 C 2 T x -ZnO composite layer and formed on the Ti 3 C 2 T x -ZnO thin film layer on the surface of the ZnO composite layer, Ti 3 C 2 T x -ZnO composite layer contains Ti 3 C 2 T x Mxene nanomaterials and ZnO nanomaterials; the second electrode layer is distributed with gas supply and the Ti 3 C 2 T x -Through holes contacting the ZnO composite layer and / or the ZnO thin film layer. CN116297694A discloses a Ni-doped sheet ZnO / MXene nanocomposite acetone gas sensor, and CN117538380A discloses an accordion-shaped MXene in-situ generated TiO 2 Nanosheet composite ZnO nanomaterial and high-sensitivity room temperature gas sensor. CN102628824A discloses a gas sensor based on hydrotalcite.n2+ and M 3+ NaOH is added to the mixed salt solution, and then hydrothermal crystallization, washing, and drying are performed to obtain a semiconductor material containing ZnO. The semiconductor material is then added to a solvent to prepare a paste, which is then coated on the surface of a ceramic tube and aged at the melting point.
[0006] However, the gas sensors obtained from the above patents cannot detect triethylamine gas well at low temperatures. Triethylamine is a volatile organic compound, which is widely used in various compound industries as a reactant, catalyst, solvent, etc. It is highly toxic, flammable, and difficult to degrade. The triethylamine gas content needs to be monitored. In addition, fish and seafood will release triethylamine when they rot, and the freshness can be quickly judged by the triethylamine concentration. According to the Occupational Safety and Health Administration, the volume concentration of triethylamine in the workplace is 10×10 -6 Therefore, the preparation of sensitive triethylamine sensors is of great significance in the fields of environmental monitoring and food safety. Summary of the invention
[0007] In order to solve the shortcomings of the prior art gas sensors for triethylamine detection, such as high detection temperature and poor detection effect, the present invention uses an electrostatic self-assembly method to mix divalent metal ions, trivalent metal ions, and tetravalent metal ions in a specific ratio, add alkali solution, perform hydrothermal reaction, calcine, and composite the obtained product with MXene. The obtained composite material is prepared as a gas sensor, and the obtained gas sensor has an excellent detection effect for triethylamine at a relatively low working temperature. Specifically, the present invention provides the following technical solutions:
[0008] A method for preparing a multi-metal doped metal oxide / MXene composite gas sensor comprises the following steps:
[0009] (S1) Preparation of soluble metal cation Cd 2+ , La 3+ and Sn 4+ Mixed salt solution, Cd 2+ , La 3+ and Sn 4+ The molar ratio of is 1.5-3:0.2-0.6:5-10, the pH is adjusted to 8-9, the temperature is raised and stirred, washed, dried, and calcined to obtain a multi-metal doped metal oxide;
[0010] (S2) The multi-metal doped metal oxide is dispersed in an ionic surfactant with a concentration of 5-20 g / L, stirred, washed, and dried to obtain a modified multi-component metal doped metal oxide.
[0011] (S3) dispersing the modified multi-metal doped metal oxide in water, adding MXene, stirring, washing, and drying to obtain a multi-component metal doped metal oxide / MXene semiconductor composite material;
[0012] (S4) The multi-component metal-doped metal oxide / MXene semiconductor composite material and a solvent are mixed into a paste, coated on the surface of a ceramic tube, dried, and electrically aged to prepare a gas sensor.
[0013] Furthermore, in step (S1), the concentration of each metal ion in the mixed salt solution is not particularly limited, such as Cd 2+ The concentration is 0.05-0.5mol / L.
[0014] Furthermore, in step (S1), NaOH and / or KOH are used to adjust the pH, the temperature is stirred at 60-90°C for 5-10h, and the drying is not particularly limited, such as drying at 60-80°C to constant weight; the calcination is heated to 500-900°C at a heating rate of 1-10°C / min and calcined for 1-4h. 2+ , La 3+ and Sn 4+ The molar ratio is 2.5-3:0.2-0.4:5.
[0015] Further, in step (S2), the ionic surfactant is selected from at least one of anionic surfactants, cationic surfactants, and amphoteric surfactants; preferably, the anionic surfactant is selected from at least one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; the cationic surfactant is selected from at least one of dodecylmethylethylbenzylammonium chloride, tetradecylmethylethylbenzylammonium chloride, hexadecylmethylethylbenzylammonium chloride, and hexadecyltrimethylammonium bromide; the amphoteric surfactant is an imidazole-type amphoteric surfactant and / or Betaine type amphoteric surfactant; the imidazole type amphoteric surfactant is selected from at least one of 2-dodecyl-N-hydroxyethyl-N-carboxymethyl imidazoline, 2-undecyl-N-methyl-N-ethyl imidazoline, 2-tetradecyl-N-ethyl-N-ethyl imidazoline, and 2-tetradecyl-N-ethyl-N-hydroxyethyl imidazoline; the betaine type surfactant is selected from at least one of lauryl hydroxysulfonyl betaine, cocoyl propyl betaine, lauroyl propyl betaine, lauroyl propyl hydroxysulfonyl betaine, and cocamide hydroxysulfonyl betaine. Stirring is performed at 15-30°C for 12-24 hours.
[0016] Preferably, the ionic surfactant is an imidazoline-based amphoteric surfactant. The inventors unexpectedly discovered that adding a certain amount of imidazoline-based amphoteric surfactant in step S2 can significantly improve the stability of the obtained gas sensor.
[0017] Furthermore, in step (S3), the mass ratio of the multi-metal doped metal oxide to MXene is 100:2-8. The introduction of an appropriate amount of MXene can enhance the conductivity of the material, provide reaction sites for gas sensing, and also reduce the accumulation of oxide nanoparticles. The introduction of excessive MXene will lead to the accumulation of MXene sheets, affecting the transmission of electrons during the gas sensing reaction. If the amount is too small, the effect of MXene cannot be reflected.
[0018] Furthermore, in step (S3), the concentration of the multi-metal doped metal oxide dispersed in water is 1-20 mg / L, preferably 5-10 mg / L, and the stirring is performed at 15-30° C. for 8-24 hours.
[0019] Furthermore, in step (S3), the MXene is selected from Ti 3 C 2 T x 、Ti 3 N 2 T x At least one of .
[0020] Furthermore, in step (S4), the solvent is selected from water, ethanol, or a mixed solvent of the two, and the ratio of the multi-component metal-doped metal oxide / MXene semiconductor composite material to the solvent is 40-100 mg: 0.15-0.3 mL.
[0021] Furthermore, in step (S4), the condition for power-on aging is that the ceramic tube is placed on an aging table, a current of 80-120 mA is set, and aging is performed for 12-24 hours.
[0022] The present invention also provides use of the multi-metal-doped metal oxide / MXene composite material gas sensor in detecting triethylamine gas.
[0023] MXene, as a supporting material, promotes the uniform anchoring of multi-metal doped metal oxides, while giving the material a larger specific surface area, thereby capturing more gases, high gas-sensitive response values and selectivity. The inventors found that among many gases, the gas-sensitive element prepared by the present invention also has outstanding sensitivity and fast response / recovery time to triethylamine at a lower operating temperature. It may be that the special structure provides more active sites for the adsorption of triethylamine molecules, which is conducive to the diffusion and penetration of gases in the sensing layer. A pn heterojunction can be formed between the MXene flakes and the multi-metal doped metal oxides, so that the composite material can have a higher response and a fast response recovery time at a lower operating temperature. The rapid real-time detection of triethylamine gas is of great significance in the field of food safety.
[0024] The present invention also provides a method for detecting triethylamine gas content, comprising the following steps:
[0025] The optimal working current of the multi-metal doped metal oxide / MXene composite gas sensor to triethylamine was determined, and the temperature-sensitivity curve was obtained. Under this current condition, the sensitivity of the gas sensor to different concentrations of triethylamine was tested to obtain the sensitivity-concentration curve. According to the curve fitting, the unknown concentration of triethylamine gas was tested.
[0026] Specifically, the test of the gas-sensitive performance of triethylamine for gas sensors was carried out in the CGS-8 test system. First, place the gas sensor in the chamber of the test system and cover it with the glass cover. Then turn on the heating system of the gas sensor. The working temperature of the gas sensor can be adjusted by adjusting the current in the heating system. After starting the acquisition, let the initial resistance of the sensor reach a stable value Ra, and then start the formal acquisition. Before injecting the triethylamine liquid, turn on the heating evaporation button outside the chamber, use a micro-injector to measure a certain volume of triethylamine liquid after conversion and inject it into the evaporating dish in the chamber. The liquid will evaporate into a gas of corresponding concentration, and then the resistance will change to a certain extent until it stabilizes to a value Rg. Finally, remove the glass cover, turn on the fan, let in air, stop collecting after the resistance stabilizes, and save the obtained data for subsequent analysis. Save the obtained data. The gas sensitivity value excited by ultraviolet light is defined as S=Ra / Rg.
[0027] Gas-sensing test: The gas-sensing element test system consists of two parts: hardware and software. The system hardware consists of a PC, cables, gas distribution box, etc. The experimental instruments include gas-sensing elements, extension cords, etc. First, determine the best working current of this gas-sensing element for different gases, and measure the sensitivity of the gas-sensing element to gases of different concentrations (10-50000ppm) under this current to obtain the corresponding curve; then measure the sensitivity of this gas-sensing element to gases of a specific concentration to obtain the response recovery curve.
[0028] The advantages of the present invention are: simple preparation steps, low cost, uniform distribution of element composition, and diversified and uniform distribution of element composition of the composite material; the prepared gas sensor has high sensitivity, fast response recovery, good stability, great development potential, and is conducive to promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The sensitivity concentration curve of the gas sensor to triethylamine gas obtained in Example 1 is shown.
[0030] Figure 2 The response recovery curve of the gas sensor to 100 ppm triethylamine gas obtained in Example 1 is shown.
[0031] Figure 3 This is a comparison chart of the sensitivity of the gas sensor obtained in Example 1 to different gases at 100 ppm.
[0032] Figure 4 The diagram shows the optimal operating temperature and sensitivity of the gas sensor prepared in Examples 1-3 to 100 ppm triethylamine gas.
[0033] Figure 5 This is the best working temperature-sensitivity diagram of the gas sensor prepared in comparative example 1 to 100ppm triethylamine gas.
[0034] Figure 6 The La / Cd co-doped SnO of Example 1 2 / Ti 3 C 2 T x MXene composites and La / Cd co-doped SnO of Comparative Example 1 2 XRD pattern of .
[0035] Figure 7 The La / Cd co-doped SnO prepared in Example 1 2 / Ti 3 C 2 T x SEM image of MXene.
[0036] Figure 8 The La / Cd co-doped SnO prepared in Example 8 2 / Ti 3 C 2 T x SEM image of MXene. DETAILED DESCRIPTION
[0037] The present invention is explained and illustrated by way of specific embodiments below.
[0038] Example 1
[0039] 1. Preparation of multi-component bimetallic doped oxides / MXene by electrostatic self-assembly:
[0040] 2.5mmol Cd(NO 3 ) 2 ·4H 2 O and 5 mmol SnCl 4 ·5H 2 O and 0.4 mmol La(NO 3 ) 3 6H 2O was dissolved in 40 ml of water and stirred for 30 minutes until transparent. 1 M NaOH was added to the solution until the pH value was 9. After stirring for 20 minutes, it was transferred to a water bath and stirred at 80 ° C for 6 hours. After cooling, it was washed with deionized water several times and dried in an oven at 60 ° C for 12 hours. The obtained precursor was calcined at 600 ° C for 1 hour with a heating rate of 2 ° C / min. The obtained La / Cd co-doped SnO 2 (La / Cd-SnO 2 ) was dispersed in an aqueous solution of 10 g / L 2-dodecyl-N-hydroxyethyl-N-carboxymethylimidazoline, stirred at 30 °C for 24 h, washed, and dried to obtain the modified La / Cd-SnO 2 Weigh 0.2g of the modified La / Cd-SnO 2 Dissolve in 40 ml of deionized water, stir for 30 minutes, and then add La / Cd-SnO 2 4% Ti by mass 3 C 2 T x MXene was stirred at room temperature for 18 h, washed and dried in a vacuum oven at 60 °C for 12 h to obtain La / Cd co-doped SnO 2 / Ti 3 C 2 T x MXene composites.
[0041] 2. Add 0.05 g of La / Cd co-doped SnO obtained in step 1 into an agate mortar. 2 / Ti 3 C 2 T x The MXene composite material is ground evenly, and then 0.2 mL of deionized water is added. After it is adjusted into a paste, it is evenly applied to the outside of the ceramic tube with a fine brush. The coated ceramic tube is placed in a porcelain ark and dried in an oven at 30°C for 1 hour, and then naturally cooled for use. The four electrode wires of the ceramic tube are welded to the base, and then the heating wire is passed through the ceramic tube and its two ends are also welded to the base. The welded gas sensor is placed on a special aging table, set to 80 mA current, and aged for 12 hours to obtain a gas sensor.
[0042] 3. The test of the gas-sensitive performance of triethylamine by the gas sensor was carried out in the CGS-8 test system. First, place the gas sensor in the chamber of the test system and cover it with the glass cover. Then turn on the heating system of the gas sensor. The working temperature of the gas sensor can be adjusted by adjusting the current in the heating system. After starting the acquisition, let the initial resistance of the sensor reach a stable value Ra, and then start the formal acquisition. Before injecting the triethylamine liquid, turn on the heating evaporation button outside the chamber, use a micro-injector to measure a certain volume of triethylamine liquid after conversion and inject it into the evaporating dish in the chamber. The liquid will evaporate into a gas of corresponding concentration, and then the resistance will change until it stabilizes to a value Rg. Finally, remove the glass cover, turn on the fan, let in air, stop collecting after the resistance stabilizes, and save the obtained data for subsequent analysis. Save the obtained data. The sensitivity value is defined as S=Ra / Rg.
[0043] 4. The stability performance test of the triethylamine gas-sensitive performance of the gas-sensitive element is carried out in the CGS-8 test system. The test method is the same as step 3 above. The difference is that the stability test is a periodic regular test of the gas-sensitive element. The performance test of the gas-sensitive element is carried out every 5 days, and a total of 5 rounds of tests are carried out. The data is recorded at the same time. The stability is measured by the variance formula. The smaller the variance, the better the stability.
[0044] Example 2
[0045] The other conditions are the same as those in Example 1, except that in step 1, Ti 3 C 2 T x The amount of MXene added is La / Cd-SnO 2 8% of mass.
[0046] Example 3
[0047] The other conditions are the same as those in Example 1, except that in step 1, Ti 3 C 2 T x The amount of MXene added is La / Cd-SnO 2 2% of mass.
[0048] Figure 1 This is the sensitivity concentration curve of the gas sensor obtained by the electrostatic self-assembly method in Example 1 to triethylamine gas.
[0049] Figure 2 This is the response recovery curve of the gas sensor obtained by the electrostatic self-assembly method in Example 1 to 100 ppm triethylamine gas.
[0050] Figure 3This is a comparison chart of the sensitivity of the multi-metal doped metal oxide / MXene gas sensor to different gases at 100 ppm obtained by the electrostatic self-assembly method in Example 1. It can be seen that the gas sensor prepared in Example 1 has excellent selectivity for triethylamine.
[0051] Figure 4 The best working temperature and sensitivity curve of the gas sensors prepared in Examples 1-3 to 100ppm triethylamine gas. It can be seen that the best working temperature of the gas sensors in Examples 1-3 is 200°C, and the sensitivities of the gas sensors in Examples 1, 2 and 3 to 100ppm triethylamine are 58.2, 39.6 and 29.9 respectively.
[0052] Example 4
[0053] The other conditions were the same as those in Example 1, except that in step 1, the amounts of Cd, Sn, and La were changed to: 1.5 mmol Cd(NO 3 ) 2 ·4H 2 O and 5 mmol SnCl 4 ·5H 2 O and 0.6 mmol La(NO 3 ) 3 6H 2 O.
[0054] Example 5
[0055] The other conditions were the same as those in Example 1, except that in step 1, the amounts of Cd, Sn, and La were changed to: 3 mmol Cd(NO 3 ) 2 ·4H 2 O and 5 mmol SnCl 4 ·5H 2 O and 0.2 mmol La(NO 3 ) 3 6H 2 O.
[0056] Example 6
[0057] The other conditions were the same as those in Example 1, except that in step 1, the amounts of Cd, Sn, and La were changed to: 2.5 mmol Cd(NO 3 ) 2 ·4H 2 O and 10 mmol SnCl 4 ·5H 2 O and 0.4 mmol La(NO 3 ) 3 6H 2 O.
[0058] Example 7
[0059] The other conditions were the same as those in Example 1, except that in step 1, the amphoteric surfactant 2-dodecyl-N-hydroxyethyl-N-carboxymethylimidazoline was replaced by an anionic surfactant SDS of equal mass concentration.
[0060] Example 8
[0061] The other conditions are the same as those in Example 1, except that in step 1, the amphoteric surfactant 2-dodecyl-N-hydroxyethyl-N-carboxymethylimidazoline is replaced by a cationic surfactant CTAB of equal mass concentration.
[0062] Example 9
[0063] The other conditions are the same as those in Example 1, except that in step 1, the amphoteric surfactant 2-dodecyl-N-hydroxyethyl-N-carboxymethylimidazoline is replaced by an amphoteric surfactant cocoylpropyl betaine of equal mass concentration.
[0064] Comparative Example 1
[0065] The other conditions are the same as those in Example 1, except that La / Cd co-doped SnO is prepared in step 1. 2 After that, La / Cd is directly co-doped into SnO 2 Made into a gas sensor.
[0066] Figure 5 This is the working temperature-sensitivity diagram of the gas sensor of Example 1. It can be seen that compared with Example 1, its optimal working temperature is increased and its sensitivity is decreased. This shows that MXene and La / Cd co-doped SnO 2 After compounding, the performance of gas-sensitive elements in detecting triethylamine can be significantly improved.
[0067] Figure 6 The La / Cd co-doped SnO of Example 1 2 / Ti 3 C 2 T x MXene composites and La / Cd co-doped SnO of Comparative Example 1 2 XRD diagram. It can be seen that the amount of MXene added is much smaller than that of La / Cd co-doped SnO 2 The amount of La / Cd co-doped SnO 2 / Ti 3 C 2 T x MXene composite materials mainly show SnO 2The La feed amount is much smaller than the Sn feed amount, so there is no La oxide peak; a small amount of CdSnO 3 , so we can see that CdSnO 3 Weak peak, but the main peak is still reflected in SnO 2 .
[0068] Figure 7 and Figure 8 The La / Cd co-doped SnO prepared in Example 1 and Example 8 are respectively 2 / Ti 3 C 2 T x From the SEM image of MXene, it can be seen that in Example 1, the composite prepared in the amphoteric surfactant environment is better composited, and the oxide nanoparticles are more evenly distributed on the accordion-shaped MXene, while the distribution of the composite oxide nanoparticles prepared in the cationic ionic surfactant environment of Example 8 is more dispersed and cannot be well concentrated on the MXene surface.
[0069] Comparative Example 2
[0070] The other conditions were the same as those in Example 1, except that in step 1, 0.4 mmol La(NO 3 ) 3 6H 2 O.
[0071] Comparative Example 3
[0072] The other conditions are the same as those in Example 1, except that in step 1, La(NO 3 ) 3 6H 2 O was replaced by an equimolar amount of Ce(NO 3 ) 3 6H 2 O.
[0073] Comparative Example 4
[0074] The other conditions were the same as those in Example 1, except that in step 1, Cd(NO 3 ) 2 ·4H 2 O was replaced by an equimolar amount of Zn(NO 3 ) 2 6H 2 O.
[0075] The test results of the gas sensors of the above examples and comparative examples for 100 ppm triethylamine at an operating temperature of 200° C. are listed in the following Table 1.
[0076] Table 1 Detection performance of gas sensor for triethylamine
[0077]
Claims
1. A method for preparing a multi-metal doped metal oxide / MXene composite gas sensor, characterized in that: The following steps are involved: (S1) Preparation of soluble metal cation Cd 2+ , La 3+ and Sn 4+ Mixed salt solution, Cd 2+ , La 3+ and Sn 4+ The molar ratio of is 1.5-3:0.2-0.6:5-10:, adjusting the pH to 8-9, heating and stirring, washing, drying, and calcining to obtain a multi-metal doped metal oxide; (S2) dispersing the multi-metal doped metal oxide in an ionic surfactant at a concentration of 5-20 g / L, stirring, washing, and drying to obtain a modified multi-component metal doped metal oxide; (S3) dispersing the modified multi-metal doped metal oxide in water, adding MXene, stirring, washing, and drying to obtain a multi-component metal doped metal oxide / MXene semiconductor composite material; (S4) The multi-component metal-doped metal oxide / MXene semiconductor composite material and a solvent are mixed into a paste, coated on the surface of a ceramic tube, dried, and electrically aged to prepare a gas sensor.
2. The preparation method according to claim 1, characterized in that: In step (S1), in the mixed salt solution, Cd 2+ The concentration is 0.05-0.5 mol / L; NaOH and / or KOH are used to adjust the pH, and the temperature is stirred at 60-90°C for 5-10h; the calcination is heated to 500-900°C at a heating rate of 1-10°C / min and calcined for 1-4h.
3. The preparation method according to claim 1, characterized in that: In step (S1), Cd 2+ , La 3+ and Sn 4+ The molar ratio is 2.5-3:0.2-0.4:
5.
4. The preparation method according to claim 1, characterized in that: In step (S2), the ionic surfactant is selected from at least one of anionic surfactants, cationic surfactants, and amphoteric surfactants; preferably, the anionic surfactant is selected from at least one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; the cationic surfactant is selected from at least one of dodecylmethylethylbenzylammonium chloride, tetradecylmethylethylbenzylammonium chloride, hexadecylmethylethylbenzylammonium chloride, and hexadecyltrimethylammonium bromide; the amphoteric surfactant is an imidazole-type amphoteric surfactant and / or betaine The imidazole type amphoteric surfactant is selected from at least one of 2-dodecyl-N-hydroxyethyl-N-carboxymethyl imidazoline, 2-undecyl-N-methyl-N-ethyl imidazoline, 2-tetradecyl-N-ethyl-N-ethyl imidazoline, and 2-tetradecyl-N-ethyl-N-hydroxyethyl imidazoline; the betaine type surfactant is selected from at least one of lauryl hydroxysulfonate, cocoyl propyl betaine, lauroyl propyl betaine, lauroyl propyl hydroxysulfonate betaine, and cocamide hydroxysulfonate.
5. The preparation method according to claim 4, characterized in that: The ionic surfactant is an imidazoline-based amphoteric surfactant.
6. The preparation method according to claim 1, characterized in that: In step (S3), the mass ratio of the multi-metal doped metal oxide to MXene is 100:2-8.
7. The preparation method according to claim 1, characterized in that: In step (S3), the concentration of the multi-metal doped metal oxide dispersed in water is 1-20 mg / L, preferably 5-10 mg / L.
8. The preparation method according to claim 1, characterized in that: In step (S3), the MXene is selected from Ti3C2T x 、Ti3N2T x At least one of .
9. The preparation method according to claim 1, characterized in that: In step (S4), the solvent is selected from water, ethanol, or a mixed solvent of the two, and the ratio of the multi-component metal-doped metal oxide / MXene semiconductor composite material to the solvent is 40-100 mg: 0.15-0.3 mL; the condition for power aging is that the ceramic tube is placed on an aging table, a current of 80-120 mA is set, and aging is performed for 12-120 hours.
10. Use of a multi-metal doped metal oxide / MXene composite material gas sensor prepared by the preparation method according to any one of claims 1 to 9 in detecting triethylamine gas.
Citation Information
Patent Citations
Gas sensitive element taking houghite as precursor and preparation method thereof
CN102628824A
Preparation method of Ni-doped flaky ZnO / MXene nano-composite acetone gas-sensitive sensing material
CN116297694A
Organ-shaped Mxene in-situ generated TiO2 nanosheet composite ZnO nano material and preparation method of high-sensitivity room-temperature gas sensor
CN117538380A
Flexible gas sensor as well as preparation method and application thereof
CN118937421A